Experimental study of the influence of consumers movement parallel to the frontal opening of a multideck display case on the evaporator's thermal performance - Heidinger, Gustavo Galdi (2019)
This paper reports the results of experimental tests performed according to ISO 23953 (climate class n° 3: 25ºC and 60%) in an open refrigerated multideck display case (ORDC) to evaluate the influence of consumers passing in front of its opening on the thermal performance of the evaporator. The consumers’ passage in front of the ORDC is simulated by a robotic mannequin: MARIA - Mannequin for Automatic Replication of the Interference in the Air curtain. Tests are performed for MARIA velocity's ranging from 0.2 ms-1 to 0.8 ms-1, with 0.2 ms-1 velocity steps for two conditions: mannequin moving towards or against the airflow of the test room. All tests are performed in an ORDC with dual air curtain. The results quantify the influence of MARIA translational velocity on the frost formation in the evaporator coil and how this phenomenon affects the evaporator's airflow, inlet and outlet temperatures and sensible and latent heat loads. The analysis of experimental data provides valuable information for evaporator design taking into account usual in-store conditions.